Dual Secure Cryptographic Measures by Two-Phase Locking Protocol - Hassan, Shabbir (International Journal of Computer Sciences and Engineering, 2020)
Sender sends the lock of an encrypted binary number of a locker crisp value from a Fuzzy Membership Table which is defined on ASCII values of uppercase alphabets and membership function. The receiver then converts the binary number into a fuzzy number and then it is de-fuzzified using a suitable formula. In terms of area costs, computing resources, web services, and full capabilities, Smart Grid are considered to be the enhancements over the existing grid system. The future domain of the missions in the region is described by smart energy, smart grids, intelligent homes, and clever cities as the ambitious flagship programmer of the Indian digital initiative. More than 100 intelligent cities in India are expected for ICT-led solutions with big data analytics. The exponential growth of smart grids has posed several safety dangers, cyber threats, and data protection as a nation's security. Smart grids, made up of numerous networks, intelligent control, access control, and power grid equipment, are more likely to be exposed to network security and cyber-attacks potentially interrupting delivery in a city. The paper present a software-oriented binary grid system (a Two-Phase Locking Protocol) and problems associated with the intelligent grid system and discusses the use of smart grid smart hardware using the Advanced Encryption Standard (AES). To ensure that AES can be employed in the intelligent grid and communication infrastructure. The Xilinx ISE 14.2 software has designed the AES encryption and decryption unit and is synthesized in SPARTAN-3E FPGA to test for certain cases.